Pembatalan Akta Hibah Akibat Pelanggaran Hak Mutlak Ahli Waris Legitimaris : (Putusan Mahkamah Agung Nomor 2954K/PDT/2017) - Sebayang, Nurhalimah Br; Purba, Hasim; T. Keizerina Devi A. (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
This research aims to analyze, (1) legal protection of the absolute rights of legitimate heirs in cases of gifts that violate the legitime portie; (2) legal consequences related to the cancellation of the gift deed due to violation of the absolute rights of the legitimate heirs; (3) as well as analyzing the judge's legal considerations in canceling the gift deed due to a violation of the absolute rights of the legitimate heir. The legal theories used are the theory of legal protection, legal consequences and judge's consideration. The research method used is normative juridical. The primary source of material comes from statutory regulations relating to grants, namely the KUHPerdata and Putusan Mahkamah Agung No. 2954K/Pdt/2017, while secondary data comes from books, magazines, scientific journals, articles, free articles from the internet and newspaper. The results of this research are (1) regarding the grant deed in the aquo case, the author found that there were several conditions that were not fulfilled in granting the grant, making the status of the grant deed considered legally defective and therefore null and void; (2) Because the deed of gift is null and void and causes harm to the subjective rights of other heirs, the judge's decision regarding land that cannot be divided is based on legitiieme portie to be auctioned.